Dietary factors associated with anaemia among pregnant women attending antenatal care clinics in Sekota town, Northern Ethiopia: a facility-based cross-sectional study - Kassahun Ayele; Meron Demisew (BMJ Publishing Group, 2024)
Background Anaemia is a major public health problem during pregnancy, especially in developing countries such as Ethiopia. Poor diet patterns are common contributors to anaemia. This study assessed the dietary factors associated with anaemia among pregnant women attending antenatal care clinics in Sekota town, Northern Ethiopia.Methods A facility-based cross-sectional study was conducted from June to August 2021 among 367 pregnant women who were selected using systematic random sampling techniques. A structured questionnaire was used to collect sociodemographic, obstetric and dietary data. The nutritional status of pregnant women was assessed using a mid-upper arm circumference measuring tape, and haemoglobin levels were tested using the haematocrit centrifugation technique. The data were analysed using SPSS V.21. Bivariate and multivariate logistic regression analyses were performed to assess dietary factors associated with anaemia and p<0.05 was used to declare statistical significance.Results Dietary pattern predictors such as meal frequency (adjusted OR (AOR)=0.27, 95% CI: 0.12, 0.59), meat consumption frequency (AOR=4.05, 95% CI: 2.46, 33.65), fruit and vegetable consumption frequency (AOR=2.88, 95% CI: 2.08, 26.81), Dietary Diversity Score (AOR=12.81, 95% CI: 3.93, 41.75), food aversion (AOR=0.12, 95% CI: 0.03, 0.47) and undernutrition (AOR=0.22, 95% CI: 0.07, 0.64) were significantly associated with anaemia.Conclusion Predictors of dietary pattern, such as meal frequency, Dietary Diversity Score, food aversion, meat consumption frequency, fruit and vegetable consumption frequency, and undernutrition were significantly associated with anaemia among pregnant women in the study area. Therefore, healthcare providers, policymakers, researchers and other stakeholders should pay special attention to maternal dietary patterns to address the identified factors. Programmes should be developed and implemented to improve optimal dietary patterns and proper nutrition during pregnancy to overcome anaemia and other pregnancy complications.